Spinal Trauma is Never without Sin: A Tetraplegia Patient Presented Without any Symptoms - EFEOGLU, Melis (Turk J Emerg Med, 2016)
Spinal cord injuries are amongst the most dangerous injuries, leading to high mortality and morbidity. Injured patients are occasionally faced with life-threatening complications and quality-of-life changing neurological deficits. Thoracic and cervical spinal segments are the most effected sites of injury and a wide range of complications including paraplegia, respiratory and cardiovascular compromise secondary to autonomic dysfunction or tetraplegia may ensue. We aim to draw attention to the progressive nature of the neurological deficits in a patient admitted asymptomatically. Also, we would like to discuss the importance of swift diagnosis and management in such patients. In asymptomatic patients in whom no fractures are diagnosed with CT scans, a neurological examination should be repeated several times to exclude any neurological injuries that were missed. MRI should be ordered in an emergency setting even though it is not frequently used as a diagnostic modality. This should be done especially in patients without any fractures on CT but with neurological signs.